Penerapan Metode Pembelajaran Demonstrasi Animasi 3d Pada Mata Pelajaran Konstruksi Utilitas Gedung Menggunakan Software SketchUp - Ahmad Yudi Mubarroq; Muhammad Aris Ichwanto; Akhmad Sokhe (Universitas Islam Raden Rahmat, Malang, 2024)
This research was conducted at SMKN 1 Ngasem, Kediri Regency. The research focused on the Building Modeling and Information Design (DPIB) department, especially in the building utility construction map. Students are quite difficult in understanding and recognizing the parts of the building and their functions, because the previous learning is considered less effective because it relies on the lecture method. The purpose of this study was to analyze student learning outcomes before and after being given treatment using the 3d animation demonstration learning method using SketchUp software. The research method used by researchers in this study uses a quantitative approach by applying a Quasi-experiment design: One-Group Pretest-Postest was conducted on one class with 36 students. Data analysis was carried out by comparing the average pre-test and post-test scores using the paired sample t-test test. The results of the analysis showed a significant increase with a significance value of <0.001 (Sig <0.05), indicating that the use of the demonstration learning method is effective in improving student understanding.